N-heterocyclic carbene-catalyzed [4 + 2] cyclization of 2-bromo-2-enal with 3-alkylenyloxindoles: efficient assembly of spirocarbocyclic oxindole. Issue 6 (15th December 2014) - Xie, Yuanwei; Que, Yonglei; Li, Tuanjie; Zhu, Ling; Yu, Chenxia; Yao, Changsheng
Abstract : A NHC-catalyzed [4 + 2] cyclization of 2-bromo-2-enal bearing γ-H with 3-alkylenyloxindoles under mild reaction conditions gives spirocarbocyclic oxindoles containing one quaternary carbon with high diastereoselectivies. Abstract : A NHC-catalyzed [4 + 2] cyclization of 2-bromo-2-enal bearing γ-H with 3-alkylenyloxindoles under mild reaction conditions gives spirocarbocyclic oxindoles containing one quaternary carbon in moderate to good yields with high diastereoselectivities. The easy availability of the starting materials, the concise assembly and the potential utilization value of the products make this strategy attractive in molecular biology and pharmacy.